EFEKTIFITAS BAHAN AJAR BERBENTUK KOMIK MATERI SISTEM PERNAPASAN DI MTs AL-ISLAM SUMURREJO KOTA SEMARANG (FMIPA UNNES, 2014)
This study aims to test the effectiveness of teaching materials in the form comic material respiratory system and analyze the correlation between student’s interest with learning outcomes MTs Al-Islam Sumurrejo. The population in this study were 8th grade classes totaling two. The samples used were two classes ie class VIII-A (experimental class) and VIII-B (grade control) taken by simple random sampling. The design of this study was Quasi Experimental kind of post-test only. Study outcomes data control group analyzed use the t-test and interest in learning, the teacher and studentsresponses data analyzed descriptively percentage. Relationship student’s interest with learning outcomes were analyzed using product moment correlation formula. The results showed that there are significant differences between the learning outcomes experiment group with control that is equal to 6.14, the average experimental group was 85, the control group was 75, 95% of students achieving KKM,, 95% of students have high learning interest to very high, 100% of teachers responding positively and 89% of students responded well, there is a positive correlation between student’s interest with learning outcomes coefficient of 0.60. Teaching materials comic respiratory system effectively applied at MTs Al-Islam Sumurrejo and positive correlation between student’s interest with learning outcomes. Penelitian ini bertujuan untuk menguji keefektifan bahan ajar berbentuk komik materi sistem pernapasan dan menganalisis korelasi antara minat belajar dengan hasil belajar siswa MTs Al-Islam Sumurrejo. Populasi dalam penelitian ini adalah kelas VIII yang berjumlah dua kelas. Seluruh populasi digunakan sebagai sampel yaitu kelas VIII-A (kelas eksperimen) dan VIII-B (kelas kontrol) yang diambil dengan teknik acak sederhana. Desain penelitian ini adalah Quasi Experimental jenis post-test only. Hasil belajar kelompok eksperimen dan kontrol dianalisis menggunakan uji t. Minat belajar, tanggapan guru maupun siswa dianalisis menggunakan teknik deskriptif persentase. Hubungan hasil belajar dengan minat belajar dianalisis menggunakan rumus korelasi product moment. Hasil penelitian menunjukkan bahwa terdapat 95,5% siswa kelompok eksperimen mencapai KKM, terdapat perbedaan yang signifikan antara hasil belajar kelompok eksperimen dengan kontrol, rata-rata hasil belajar kelompok eksperimen lebih besar dari kelompok kontrol, terdapat 95,45% siswa mempunyai minat belajar tinggi hingga sangat tinggi. Tanggapan guru adalah sangat baik dan 89% siswa menanggapi baik terhadap pembelajaran menggunakan bahan ajar komik. Terdapat korelasi positif antara minat belajar dengan hasil belajar siswa kelompok eksperimen. Simpulan yang dapat diambil adalah bahan ajar komik materi sistem pernapasan efektif diterapkan di MTs Al-Islam Sumurrejo dan terdapat korelasi positif antara minat dengan hasil belajar siswa.